Utilizing adult learning principles to understand students’ perception of integrating open-access resources into nutrition curriculum: A survey research - Kathleen M Hoss-Cruz; Haijun Kang (Adult Education Research Conference, 2017)
The purpose of this research roundtable is to discuss how principles of adult learning could be used to make sense of student experiences with an open-access resource used in a basic level nutrition course.
Keywords: open-access resource; adult learners; nutrition; adult learning theory